Побудова багатовимірної поліноміальної регресії. Активний експеримент - Pavlov, A. A.; Chekhovskiy, A. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2009)
A constructive method for restoration of multidimensional polynomial regression represented with extra description is considered. Distribution of noises is optional with unknown but finite dispersion. The solution to the problem is based on the possibility of an active experiment. Practical recommendations for using the method are proposed.